2015
DOI: 10.2174/1874944501508010017
|View full text |Cite
|
Sign up to set email alerts
|

Women´s Experiences in Accessing Maternal and Child Health Services During the Period of the Armed Conflict in the North of Mali

Abstract: Abstract:Background: During the year 2012 armed conflict in the northern regions of Mali, health care services were no longer able to run in the normal way and women's access to health services became a critical issue in those regions. Objective: The aim of this study was to explore the women's experiences in accessing maternal and child health services during the period of the armed conflict in the north of Mali. Methodology: The interviews were conducted with 28 married women between September and October 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Access to services for individuals in Northern Mali is limited and organizations report that women attempting to access maternal and child health care in Northern Mali are concerned since there are reports that Jihadists monitor health visits to ensure women don't access family planning services [2]. Estimates from the most recent humanitarian response plan state that, at present, 1.7 million individuals have compromised access to health care [6].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Access to services for individuals in Northern Mali is limited and organizations report that women attempting to access maternal and child health care in Northern Mali are concerned since there are reports that Jihadists monitor health visits to ensure women don't access family planning services [2]. Estimates from the most recent humanitarian response plan state that, at present, 1.7 million individuals have compromised access to health care [6].…”
Section: Discussionmentioning
confidence: 99%
“…1 Centre for Global Child Health, the Hospital for Sick Children, Toronto, Canada. 2 Faculty of Medicine and Odontostomatology, University of Sciences, Techniques and Technology of Bamako, Bamako, Mali. 3 University Clinical Research Center, Bamako, Mali.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was not surprising to see that the main issue experienced by women and doctors was the inaccessibility to the hospital. Many other authors have reported on the point of accessibility of care in conflict-affected countries (18)(19)(20). Damascus at the time of data collection (2012-2014) was not safe due to random mortars hitting the city and many governmental checkpoints in place.…”
Section: Discussionmentioning
confidence: 99%